2014
DOI: 10.1177/0141076814530684
|View full text |Cite
|
Sign up to set email alerts
|

Living conditions in Iraq: 10 years after the US-led invasion

Abstract: In the early 1980s, Iraq was a middle-income and rapidly developing country with a well-developed health system. A few decades later - after wars, sanctions and a violent sectarian upsurge - child and maternal health indicators have deteriorated, its poverty headcount index is at 22.9% and diseases such as cholera have remerged. Today Iraq is beset by chronic political deadlock and a complexity of economic challenges; accordingly, all aspects of life are suffering, including health. Irrespective of the monumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Another possible explanation is that traditional medicine does not play a significant role in Iraqi society. Before the American occupation of Iraq in 2003, the national healthcare system witnessed spectacular advancement [21]. Fortunately, the healthcare system has retained its capacity to cope with population primary healthcare needs.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible explanation is that traditional medicine does not play a significant role in Iraqi society. Before the American occupation of Iraq in 2003, the national healthcare system witnessed spectacular advancement [21]. Fortunately, the healthcare system has retained its capacity to cope with population primary healthcare needs.…”
Section: Resultsmentioning
confidence: 99%
“…The results were disappointing for the Iraqis. More than 60% were denied access to referral services due to unfair distribution of public hospitals and primary health centers and continuing deterioration in most social determinants of health [23,24]. Several international and local reports unanimously agreed that the 2003 invasion of Iraq, and the internal wars, and the subsequent destructions of health services significantly contributed to depriving millions of people, including refugees and internally displaced persons, from accessing health care services [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Most articles identifying physical effects (59%; 16/27) provided evidence for increased mortality—a large majority from within those articles (88%; 14/16) for infant mortality, 5,4153 a quarter (25%; 4/16) for maternal mortality, 42,47,48,52,53 and more than a third (36%; 6/16) for general mortality. 48,49,52,54,55 Reasons reported for increased mortality, especially infant and maternal mortality, included mortality from infectious disease, 5,41,45,51,54 noncommunicable diseases, 41,48 nutrition-related causes, 5,41,42,4648,51 increased poverty, 42,45,46,49 reduced access to medicines and health care, 41,42,4447,49,51 and destruction of public infrastructure. 41,42,45 Two articles (13%; 2/16) reported that compared to war or natural emergencies, the highest rates of infant mortality occurred under sanctions, concluding that prolonged sanctions are more lethal for infants and children than other sources of social and political distress.…”
Section: Direct Impact Of Sanctions On Healthmentioning
confidence: 99%